Centaur rising - Yolen, Jane (Square Fish, 2015)
In 1965, a year after Arianne thinks she sees a shooting star land in the fields surrounding her family's horse farm, a baby centaur is born and the family, already under scrutiny because Arianne's six-year-old brother has birth defects, struggles to keep the colt a secret.